Flooded House or Underwater Mortgage? The Implications of Climate Change and Adaptation on Housing, Income and Wealth - Yasmine van der Straten (Tinbergen Institute, 2023)
I study the implications of climate change and adaptation on housing and income, and wealth. I embed climate change in a redistributive growth model by introducing exposure of households and firms to extreme weather events, that damage their housing capital and physical capital, respectively. The analysis reveals that climate change is intrinsically redistributive, as it amplifies both income and wealth inequality. Low-income workers experience a relatively larger decline in income due to their exposure to climate-related damages, while the rate at which households with positive savings accumulate wealth rises. Furthermore, I find that adapting to climate change is more challenging for low-income households who are financially constrained, and the failure to reduce vulnerability to climate impacts exacerbates wealth inequality. Additionally, while houses exposed to climate risk face a price discount in the market, I demonstrate that the materialization of climate change risk puts upward pressure on house prices, as the supply of such houses becomes reduced. This general equilibrium effect is propagated and amplified over time.
Keywords: E44; G51; Q54; 330; Climate Change; Adaptation; Housing; Financial Assets; Extreme Weather Events; Income Inequality; Wealth Inequality